Pension reform and demographic crisis - Sinn, Hans-Werner (CESifo, 1999)
Based on explicit present value calculations, the paper critizises the view theat den PAYGO system wastes economic resources. In present value terms, there is nothing to be gained from a transition to a funded system even though the latter offers a permanently higher rate of return. The sum of the implicit and explicit tax burdens that result from the need to respect the existing pension claims is the same under all systems and transition strategies. Nevertheless a partial transition to a funded system may be a way to overcome the current demographic crisis because it replaces missing human capital with real capital.
Literaturverz. S. 27 - 29
Keywords: Arbeitspapier; Graue Literatur; Gesetzliche Rentenversicherung; Umlageverfahren; Rentenreform; Kapitaldeckungsverfahren; Rendite; Steuerbelastung; Vergleich; Theorie; Deutschland; Alternde Bevölkerung